Ketidakseragaman Pewarisan Dalam Penerapan Hukum Waris Secara Nasional - Sergio Felix Asalim; Sugianto Sugianto; Setyabudhi Setyabudhi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
There are three inheritance law systems in Indonesia that apply, namely inheritance law based on civil inheritance law, Islamic inheritance law and customary inheritance law. To this day, customary inheritance law still has a strong influence and is still applied in various regions in Indonesia even though the majority have adhered to Islam. This shows the complexity of the inheritance law system in Indonesia, which reflects the country's cultural and religious diversity. The differences between these three inheritance laws explain the reason why unification between these three inheritance laws is very difficult or impossible in Indonesia. This also makes it difficult to implement the regulations of The Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) to eliminate discrimination against women which is still often found in the inheritance law system in Indonesia.